2017
DOI: 10.22211/cejem/67560
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of CuO Nanoparticles by the Chemical Liquid Deposition Method and Investigation of its Catalytic Effect on the Thermal Decomposition of Ammonium Perchlorate

Abstract: Abstract:Copper oxide nanoparticles have been synthesized by the chemical liquid deposition method and characterized by means of X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The XRD and SEM results showed that the particle size was between 50 nm and 70 nm. Ammonium perchlorate (AP)-CuO nanostructures have been prepared by ex-situ mixing of AP and CuO nanoparticles, while AP/CuO nanocomposites have been obtained by in-situ growth of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…SEM indicates the spherical shape of synthesized copper oxide nanoparticles (Figure 2). Also reported that the mean particle size of CuO is about 50-70nm and the particle have good homogeneity, spherical structure, and appropriate separation [4]. The presence of oxygen (o) and copper (Cu) was revealed in the synthesized nanoparticles and shown as two peaks located between 0.4 KeV and 0.9 KeV.…”
Section: Resultsmentioning
confidence: 93%
“…SEM indicates the spherical shape of synthesized copper oxide nanoparticles (Figure 2). Also reported that the mean particle size of CuO is about 50-70nm and the particle have good homogeneity, spherical structure, and appropriate separation [4]. The presence of oxygen (o) and copper (Cu) was revealed in the synthesized nanoparticles and shown as two peaks located between 0.4 KeV and 0.9 KeV.…”
Section: Resultsmentioning
confidence: 93%
“…[25] reported that in chemically synthesized copper nanoparticles, peak values at 3414.35cm-1, 2926.45cm-1, 59.92cm-1, 1633.41 Cm-1, 1390.42cm-1, and 618.074cm-1 corresponds to O-H stretching of phenolic compound, C-H bending of aldehydes compounds, C-H stretching of alkenes and N-H bending of amines. [25].In chemically synthesized copper oxide nanoparticles, FT-IR peaks correspond to O-H stretch phenolic compounds, N-H stretch of amines, O-H stretch of Carboxylic group, N-H bending of amines, C-H stretch of aliphatic amines, C-Cl stretch of alkaloids, C-H bending of alkanes [26]. The effect of various quantities of copper oxide nanoparticles on the growth of Lady's finger Abelmoschus esculentus is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the morphology characterization of the CuO nanoparticles was investigated by FESEM, as shown in Figure 3 A. The nanoparticles have a uniform size, spherical shape, and appropriate separation [ 22 , 23 ]. Figure 3 B–F exhibit the FESEM images of Nd 2 O 3 doped CuO NPs at various concentration of Nd 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%